Barriers and motives for physical activity and sports practice among trans people: A systematic review - Oliveira, Joana (2022)
This study aimed to analyze the research conducted between 2016 and 2021, regarding barriers and motives for the practice of physical activity (PA), physical exercise (PE), and sports among trans individuals. The searches were carried out in the PubMed, Scopus, and Web of Science databases between January 2022 and April 2022, and included papers published between October 2016 and December 2021. After reading the full text of the studies, and according to the eligibility criteria previously defined, only six studies met the inclusion criteria. Internal barriers were related to body dissatisfaction and discomfort, discrimination, and fear of other people’s reactions. Regarding external barriers, sports environment, PE environment, and sports participation policies and regulations are the main factors expressed by trans individuals that hinder the practice of sports and PE. The desire to achieve a specific physical form and the role that PE plays in the preparation and/or replacement of gender-confirming surgery are the most important motives for the practice. This study highlights the importance of continuing to fight the barriers encountered in the practice of PE and sports, suggesting the main motives that could help create better interventions, plans, and inclusive policies that may help promote its practice.